Persebaran Medan Listrik akibat Proses Exothermic Welding pada Kabel Tegangan Menengah 20 kV - Saepul Rahmat; Riyani Prima Dewi (Infotekmesin, 2021)
In the 20 kV distribution system, insulated cables and conductors of fibrous and solid copper are used. Some problems on 20 kV system occur due to the line length of the lines. This obstacle occurs in the cable, mostly at the cable connection. To overcome this problem, a cable connection technique known as extothermic welding was developed. However, in this process, it is also undeniable that there is a thickening due to the contact which causes the uneven distribution of the electric field in the cable. To see the distribution of the electric field on the surface of the cable that was carried out by the exothermic welding process, a simulation was carried out in FEMM 4.2 with 3 final connection conditions, namely perfect jointing, jointing with a thickness of 0.5 mm and jointing with a thickness of 1 mm. As a result of this imperfect connection, the distribution of the electric field on the surface cable is uneven. There was a high electric field surge at the ends of the cable joint with a thickness of 1 mm and a reduced surge in the cable with a thickness of 0.5 mm at the joint. In a perfect connection, the distribution of the electric field occurs evenly.